Social skills in secondary school adolescents - Sacaca-Gemio, Lisbeth; Pilco-Vargas, Rosa (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2022)
This book is an adaptation of a research presented at the National University of the Altiplano, whose objective was to determine the social skills in adolescents of the Caya Agricultural Technical Secondary Educational Institution – Caya, Putina (Peru). According to the methodology, the study was cross-sectional descriptive with a non-experimental design. The population and the sample consisted of 39 adolescents from the first to the fifth grade of secondary education who meet the inclusion criteria of the research. The technique used was the survey and a social skills questionnaire was applied as an instrument, which reached a Cronbach’s Alpha reliability of 0.80. The results showed that 35.9% of adolescents have a low category in social skills, 38.5% have an average category in the area of ​​self-esteem and the areas of assertiveness, communication and decision making are in the low average category with 43.6 %, 33.3% and 41.0% respectively.